Atrial Fibrillation Genetic Risk and Ischemic Stroke Mechanisms. Issue 6 (June 2017) - Lubitz, Steven A.; Parsons, Owen E.; Anderson, Christopher D.; Benjamin, Emelia J.; Malik, Rainer; Weng, Lu-Chen; Dichgans, Martin; Sudlow, Cathie L.; Rothwell, Peter M.; Rosand, Jonathan; Ellinor, Patrick T.; Markus, Hugh S.; et al.
Abstract : Background and Purpose—: Atrial fibrillation (AF) is a leading cause of cardioembolic stroke, but the relationship between AF and noncardioembolic stroke subtypes are unclear. Because AF may be unrecognized, and because AF has a substantial genetic basis, we assessed for predisposition to AF across ischemic stroke subtypes. Methods—: We examined associations between AF genetic risk and Trial of Org 10172 in Acute Stroke Treatment stroke subtypes in 2374 ambulatory individuals with ischemic stroke and 5175 without from the Wellcome Trust Case-Control Consortium 2 using logistic regression. We calculated AF genetic risk scores using single-nucleotide polymorphisms associated with AF in a previous independent analysis across a range of preselected significance thresholds. Results—: There were 460 (19.4%) individuals with cardioembolic stroke, 498 (21.0%) with large vessel, 474 (20.0%) with small vessel, and 814 (32.3%) individuals with strokes of undetermined cause. Most AF genetic risk scores were associated with stroke, with the strongest association ( P =6×10 − 4 ) attributed to scores of 944 single-nucleotide polymorphisms (each associated with AF at P <1×10 − 3 in a previous analysis). Associations between AF genetic risk and stroke were enriched in the cardioembolic stroke subset (strongest P =1.2×10 − 9, 944 single-nucleotide polymorphism score). In contrast, AF genetic risk was not significantly associated with noncardioembolic stroke subtypes. Conclusions—: Comprehensive AF genetic risk scores were specific for cardioembolic stroke. Incomplete workups and subtype misclassification may have limited the power to detect associations with strokes of undetermined pathogenesis. Future studies are warranted to determine whether AF genetic risk is a useful biomarker to enhance clinical discrimination of stroke pathogeneses. Abstract : Supplemental Digital Content is available in the text.